2007
DOI: 10.1016/j.ijid.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Epstein–Barr virus (EBV) in HIV-infected patients and its relation with primary brain lymphoma

Abstract: During HIV infection PBMC-EBV load rises in comparison to healthy carriers, but decreases when immunosuppression progresses and CD4+ T cell count becomes <50/mm(3). Circulating EBV is mainly cell-associated in the HIV-infected population. Neither PBMC-EBV nor plasma-EBV loads would be useful to diagnose brain lymphoma in AIDS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
(56 reference statements)
2
13
0
Order By: Relevance
“…These results indicated a higher prevalence of EBV infection in HIV infected patients. Fellner et al in 2006 analyzed circulating EBV levels at the different stages of HIV infection and showed that EBV detection was similar in all groups with CD4+ T cell counts higher than 50/mm 3 (P > 0.05), and was significantly higher than in patients with less than 50 CD4+ T cells/mm 3 (P < 0.05) (14).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated a higher prevalence of EBV infection in HIV infected patients. Fellner et al in 2006 analyzed circulating EBV levels at the different stages of HIV infection and showed that EBV detection was similar in all groups with CD4+ T cell counts higher than 50/mm 3 (P > 0.05), and was significantly higher than in patients with less than 50 CD4+ T cells/mm 3 (P < 0.05) (14).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that immunocompromised patients have higher baseline viral levels than healthy carriers [99,100] , which decline after treatment. A search for EBV DNA is also useful in patients with EBV-related tumors, except for those with AIDS-related brain tumors in whom the blood levels are low because of the bloodbrain barrier [99,101] . In EBV-related cancers, episomal or naked EBV DNA from apoptotic tumor cells is found 35 February 12, 2012|Volume 1|Issue 1| WJV|www.wjgnet.com in serum and plasma [84,102] , which may also contain tumor cells with latent EBV infection [13] and virions from a small number of tumor cells undergoing lytic infection.…”
Section: Molecular Biologymentioning
confidence: 99%
“…Why EBV is so strongly associated with endemic Burkitt's lymphoma but not Burkitt's lymphoma in AIDS patients is not understood. Compared with healthy donors, HIV patients exhibit higher levels of circulating EBV DNA, yet no difference is demonstrated between HIV patients with and without lymphoma [10,11]. Antibody titers to EBV do not appear to correlate with subsequent risk of NHL in HIV patients, but decreases in EBV load with chemotherapy may predict improved outcomes with NHL [10,12].…”
Section: Hiv-associated Lymphomasmentioning
confidence: 99%